Innovative medical technologies for the treatment of urinary tract infections in peri- and postmenopausal women - О.V. Kravchenko (Publishing House TRILIST, 2022)
Objectives: to evaluate the effectiveness of Utipro Plus AF for uncomplicated urinary tract infections in women in the peri- and postmenopausal period. Materials and methods. The study included 45 patients aged 48-70 years with verified uncomplicated urinary tract infection. All patients received antimicrobial agents in accordance with approved guidelines. 25 women (main group) also received Utipro Plus AF, 20 women (control group) received only antimicrobial agents. The effectiveness of treatment was assessed on the 6th, 11th, 30th and 75th day of observation. Efficiency criteria were a decrease in the intensity of clinical symptoms, a decrease in the number of relapses, and bacterial sanitation based on the results of urine cultures (≤ 103 CFU/ml). Results. Clinical picture changed dramatically in the patients of the examined groups after treatment. Main group had no urinary incontinence, imperative urges to urinate, the frequency of dysuria disorders decreased by three times in this group, pain in the lower abdomen and burning sensation during urination were 5 times less common. Recurrences of urinary tract infections were noted in both groups by bacteriological and symptomatic criteria, but their frequency was much lower in the group that received Utipro Plus AF in addition to antibiotics. The number of positive results of urine cultures on the 75th day of observation decreased to 16% in the main group, and to 65% in the control group. Recurrences of urinary tract infections according to clinical criteria on the 75th day of observation were verified in 3 patients of the main group and in 12 patients in the control group. Conclusions. The medical product Utipro Plus AF effectively reduces bacteriological and clinical signs of uncomplicated urinary tract infections, which makes its use advisable as an additional agent to antibiotic therapy in women with uncomplicated urinary tract infections in peri- and postmenopausal period.